Pain treatment services; a national survey of tertiary care hospitals in Pakistan - Ahmed, Usama; Afshan, Gauhar (Journal of the Pakistan Medical Association, 2023)
Objective: To quantify pain services in Pakistan and classify them according to the International Association for the Study of Pain guidelines. Method: The study was conducted at the Aga Khan University, Karachi, from January to June 2022, and comprised data of all public and private tertiary care hospitals anywhere in Pakistan that were registered with the Pakistan Medical Council till November 25, 2021. Data was collected using a predesigned Google form. Data was obtained primarily via email and secondarily by a phone call in a structured format. The facilities providing dedicated pain management services were classified according to the International Association for the Study of Pain guidelines. Results: Of 118 hospitals, 45(38.1%) were in the public sector and 73(61.8%) were in the private sector. Overall, 78(65.2%) had no pain treatment services, while 40(34.2%) had such services. Of these 40(34.2%) facilities, 25(62.5%) were classified as pain centres, 11(27.5%) were pain clinics and 4(10%) were pain practices. In terms of per 100,000 population, there were 0.0193 pain services, 0.0351 pain physicians, 0.025 nursing staff and 0.02 administrative staff in the country. Physiotherapy was present in 37(92.5%) hospitals, psychiatry and psychology as allied services were used in 38(95%), acupuncture was integrated into the practice in 25(62.5%), while 39(97.5%) hospitals offered interventional procedures. Also, 9(22.5%) hospitals offered advanced training in pain medicine. Conclusion: A severe shortage of chronic pain services in Pakistan was found. Key Words: Chronic pain, Health resources, Multidisciplinary pain centres, Surveys and questionnaires, Allied health personnel.